2018
DOI: 10.1159/000495835
|View full text |Cite
|
Sign up to set email alerts
|

miR-202 Enhances the Anti-Tumor Effect of Cisplatin on Non-Small Cell Lung Cancer by Targeting the Ras/MAPK Pathway

Abstract: Background/Aims: KRas is usually mutated in non-small cell lung cancer (NSCLC). The mutated KRas gene is a negative prognostic indicator that promotes tumor proliferation, metastasis, and drug resistance in NSCLC, and thus has become a target for cancer therapy. This study is focused on the effects of the microRNA (miR)-202/KRas axis in regulating chemosensitivity in NSCLC. Methods: Quantitative reverse transcriptase real-time PCR analysis was performed to examine the expression of miR-202. MTT (3-(4,5-dimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…K-Ras is one of the three members of the Ras oncogene family that has been previously implicated in the carcinogen-esis of many human cancers, where K-Ras knockdown has been shown to suppress tumor cell growth and invasion ( 47 , 48 ). Recently, a number of miRNAs, including miR-202, were reported to suppress K-Ras expression and functioned as a tumor suppressor ( 49 ). The present study found that K-Ras knockdown conferred an inhibitory effect on the invasion and migration of ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…K-Ras is one of the three members of the Ras oncogene family that has been previously implicated in the carcinogen-esis of many human cancers, where K-Ras knockdown has been shown to suppress tumor cell growth and invasion ( 47 , 48 ). Recently, a number of miRNAs, including miR-202, were reported to suppress K-Ras expression and functioned as a tumor suppressor ( 49 ). The present study found that K-Ras knockdown conferred an inhibitory effect on the invasion and migration of ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Western Blot Detection: Western blot detection was performed as described in detail . In brief, the Hela cells were exposed to different concentrations of tested nano 1 – 3 for 24 h, then the cells were harvested and lysed with the cell lysis buffer [1 % NP‐40, 1 % sodium dodecyl sulfate (SDS), 150 mM NaCl, 25 mM Tris‐HCl (pH 7.6), 1 % deoxycholic acid sodium salt, 1 % PMSF] for 30 min on the ice.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, overexpression of miR-1 increases the chemosensitivity of non-small cell lung cancer cells by inhibiting autophagy (33). Furthermore, overexpression of miR-202 promotes chemosensitivity by suppressing the KRAS gene in lung adenocarcinoma (34). Notably, there also is increasing evidences that circulating miRNAs may be potential biomarkers for early diagnosis and prognosis of lung cancer (35,36).…”
Section: Discussionmentioning
confidence: 99%